The effectiveness of videos in improving toothbrushing skills and OHI-S scores: Research on intellectually disabled children in SLB N Jambi City: Research On intellectually Disabled Children In SLB N Jambi City - Sukarsih, Sukarsih; Silfia, Aida; Surayah, Surayah; Mardiah, Ainun; Reca, Reca; Muliadi, Muliadi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Based on RISKESDAS 2018, 45% of the population in Jambi experiences dental and oral health issues, but only 9.5% receive medical treatment. The proper tooth brushing behavior in Jambi is very low, at only 1%. Research shows that 70% of children with intellectual disabilities have moderate oral hygiene, and more than 50% are in poor condition. Videos have proven to be effective in improving oral hygiene and tooth brushing skills. Observations at SLBN 1 Kota Jambi indicate that 100% of children brush their teeth incorrectly and 95% have poor OHI-S status, necessitating video education for improvement. Method: This study uses a pre-experimental design with one group pre-test and post-test. Results: The statistical test output shows a p-value of 0.000 for skills and OHI-S. Since the value of 0.000 < 0.05, the hypothesis is accepted, meaning there is a difference between pre-test and post-test skills and OHI-S. It can be concluded that videos are effective in improving tooth brushing skills and reducing OHI-S in intellectually disabled students at SLBN I Kota Jambi in 2024. Conclusion: The use of educational videos has proven effective in improving tooth brushing skills and reducing OHI-S scores, reflecting improved oral hygiene among intellectually disabled students at SLBN I Kota Jambi in 2024.